(3fNHI GdCPgGf aj YLGFH GdHdOGfs - (3YHO GdQMje Hf SdjeGf QHjY GdbjSj GdCfOdSj GdZQfGWj, CHh MGeO Hf CHj GdQHjYs
(3ChdgG (B:s
(3CeG HYO abO SCdfi LeGYI ef Cgd GdYde hGdOjf Cf GPcQ dge QCjJg ef GdYLGFH s
(3BNQgG (B:s
(3hOGNgG MGQI eKd GdMeGe hGdNWH YfOge cKjQ hjMed Jdc GdfgQ s
(3HgG GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI (B_ (3HjQhJ (B(910 k23) s
Keywords: (3GdLZQGajG h GdHdOGfs